English Bill of Rights of 1689, 1 Wm. & Mary ch. 2, § 7 - (:unkn) unknown (General Publisher, 1689)
Provided a right for Protestants to have “Arms for their Defense . . . as allowed by law.”
--
Keywords: GUARANTEED RIGHT